Biotechnology and genetic resource policies: What is a genebank worth?: December 2003, Briefs 7 - Smale, Melinda; Koo, B. (2003)
It’s Not as Easy as 1, 2, 3… How much is a collection of plant genetic resources worth? Why do economists hesitate to place a value on it? Plant genetic resources generate economic value with multiple dimensions that are difficult to conceptualize. Only a few of these dimensions can be measured and related to a market price that is a basis for valuation. Scientific nuances complicate measurement. For example, the definition of the genetic unit to be valued depends on the crop and the farming-system context, and whether the units can be added together depends on how closely they resemble one another. Economics research, rather than accounting, is necessary to estimate the costs and benefits of the resources maintained in genebanks. Most genebanks have been publicly financed, and in the past there has been little demand by those who fund them to conduct economics research. Recently, however, demand for assessing the value of such collections appears to have heightened with changing intellectual property regimes and emerging biotechnology applications.